The pilgrim's progress across time: Medievalism and modernity on the road to Santiago - Genoni, Paul (Routledge, 2011)
This paper offers a reading of recent accounts of journeys on one of the great Christian pilgrimage routes, to Santiago de Compostela in north-west Spain. It focuses on the common narrative strategy of a disrupted sense of time expressed by the pilgrim-authors, and argues that this trope is intrinsic to texts that suggest that time has been ‘crossed’ and that the author has undertaken a ‘medieval’ experience. It is argued that this trope of crossing time is closely linked to two central themes of contemporary Santiago texts: the construction of the author as an authentic pilgrim, and the experience of forms of community that are outside the norm in the pilgrim's everyday life. These common themes in Santiago pilgrim narratives are said to be reflective of the authors’ distrust of modernity.